DETERMINAN KEJADIAN HEPATITIS B PADA IBU HAMIL - Hamzah, Ricda Nurhikmayanti; Handayani, Fitri; Nainggolan, Dimpu Rismawaty; Ujung, Riance Mardiana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Hepatitis B is a highly dangerous infectious disease that poses a serious threat to public health worldwide. Kalumata Health Center in Ternate City also showed alarming findings, namely there were 32 pregnant women who tested reactive Hepatitis B out of a total of 198 pregnant women recorded during 2023. The purpose of the study was to determine the determinants of the incidence of hepatitis b in pregnant women. The research design used in this study was cross sectional. The research was conducted at Kalumata Health Center, Ternate City. The study was conducted in July 2024. The population was all pregnant women totaling 198 people. The sample amounted to 120 people. The sampling technique used in this study was Accidental Sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between hepatitis B vaccine history (p value: 0.00) to the incidence of hepatitis B in pregnant women. It is recommended that pregnant women always maintain their health, avoid activities that can cause hepatitis B infection to enter the body and are aware of the dangers of the hepatitis B virus and pregnant women can seek information about the importance of conducting hepatitis B checks. So that mothers are motivated to do hepatitis B testing.Keywords: Hepatitis B, Vaccine History, Blood Transfusion History